Chronic anthropogenic disturbance mediates the bottom‐up influence of plant diversity on arthropods in tropical forests - Orou G. Gaoue; Hermann Bassoki; Anicet G. Dassou (Ecology and Evolution, 2024)
Abstract Understanding how primary productivity and diversity affect secondary productivity is an important debate in ecology with implications for biodiversity conservation. Particularly, how plant diversity influences arthropod diversity contributes to our understanding of trophic cascades and species coexistence. Previous studies show a positive correlation between plant and arthropod diversity. The theory of associational resistance suggests that plant herbivory rate will decrease with increasing plant diversity indicating feedbacks between primary diversity, productivity, and secondary productivity rates. However, our understanding of how these relations are mediated by anthropogenic disturbance is still limited. We surveyed 10 forest sites, half of which are disturbed by fire, logging, and tree pruning, distributed in two climatic zones in Benin, West Africa. We established 100 transects to record plant species and sampled arthropods using pitfall traps, ceramic plates with bait, and sweeping nets. We developed a structural equation model to test the mediating effect of chronic anthropogenic disturbance on plant diversity and how it influences arthropod diversity and abundance. Arthropod diversity increased but arthropod abundance decreased with increasing intensity of disturbance. We found no significant bottom‐up influence of the plant diversity on arthropod diversity but a significant plant diversity–arthropod abundance relationship. Some arthropod guilds were significantly affected by plant diversity. Finally, herbivory rates were positively associated with arthropod diversity. Synthesis. Our results highlight how chronic anthropogenic disturbance can mediate the functional links between trophic levels in terms of diversity and productivity. Our study demonstrated a decoupled response of arthropod diversity and abundance to disturbance. The direct positive influence of plant diversity on herbivory rates we found in our study provides counter‐support for the theory of associational resistance.